Analisis Pengaruh Kompensasi dan Motivasi terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada UKM Pia Mahen - Puspita, Aditya Novi; Sumartik, Sumartik (Innovative Technologica: Methodical Research Journal, 2023)
This study aims to determine the effect of compensation and motivation on employee performance with job satisfaction as an intervening variable in Pia Mahen SMEs. This research was conducted on 45 employees of UKM Pia Mahen using census sampling technique and classified as quantitative research. Data analysis techniques in this study are data quality test, descriptive statistical analysis, classical assumption test and hypothesis testing with the help of IBM SPSS 22 statistical software. The results of this study prove that compensation and motivation have a positive and significant effect on employee performance, compensation and motivation have a positive and significant effect on job satisfaction, job satisfaction is able to mediate compensation and motivation on employee performance.